2012
DOI: 10.1177/0887403412468884
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Sentencing Outcomes in South Carolina

Abstract: Despite sentencing reforms over the last few decades, many states failed to introduce guidelines, including South Carolina. The present article uses data collected from the now disbanded South Carolina Sentencing Commission (1982Commission ( to 2003 in order to assess the influence of gender, age, race, and type of crime. We found that females were consistently sentenced more leniently than were similarly situated males. Interactions between gender and the other variables, however, failed to gain significance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(12 citation statements)
references
References 71 publications
1
11
0
Order By: Relevance
“…As our data reveal, women in our study adhered to stereotypes of women as docile, weak, and vulnerable when they perceived it would benefit them. Their efforts to enact emphasized femininity in the hopes of receiving better police treatment are consistent with the chivalry hypothesis, which finds women who adhere to traditional, heteronormative gender expectations are treated more leniently ( Branscombe & Owen, 1991 ; Franklin & Fearn, 2008 ; Koons-Witt, 2002 ; Koons-Witt et al, 2014 ).…”
Section: Resultssupporting
confidence: 57%
“…As our data reveal, women in our study adhered to stereotypes of women as docile, weak, and vulnerable when they perceived it would benefit them. Their efforts to enact emphasized femininity in the hopes of receiving better police treatment are consistent with the chivalry hypothesis, which finds women who adhere to traditional, heteronormative gender expectations are treated more leniently ( Branscombe & Owen, 1991 ; Franklin & Fearn, 2008 ; Koons-Witt, 2002 ; Koons-Witt et al, 2014 ).…”
Section: Resultssupporting
confidence: 57%
“…In terms of criminal sentencing, studies have also found that women are sentenced more leniently than men (Doerner & Demuth, 2014; Koons-Witt, Sevigny, Burrow, & Hester, 2014; Spohn, 1999), though the type of crime committed (Rodriguez, Curry, & Lee, 2006), age of the offender (Steffensmeier, Ulmer, & Kramer, 1998), and incarceration decisions (jail vs. prison) can affect these relationships (Freiburger & Hilinski, 2013). Rodriguez and colleagues (2006) found that for both property- and drug-offending women were less likely to be sentenced to prison and also received shorter sentences.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although studies conducted in the South conclude that generally, women receive greater leniency in sentencing than men, this chivalry is dependent on a woman's race/ethnicity, type of crime committed, and seriousness of the offense (Koons-Witt et al, 2014;Crawford, 2000). For example, a study using data from the South Carolina Sentencing Commission from 1982-2003 found that women were sentenced more leniently than men in terms of both the decision to incarcerate and sentence length, supporting the chivalry hypothesis (Koons-Witt et al, 2014). Women were denied leniency, however, as their crimes increased in severity.…”
Section: Women's Journeys Through the Prison System From Sentencing T...mentioning
confidence: 99%